2023
DOI: 10.3390/jcm12062150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traditional Chinese Exercises on Patients with Chronic Heart Failure (TCE-HF): A Systematic Review and Meta-Analysis

Abstract: Exercise-based cardiac rehabilitation is safe and effective for chronic heart failure (CHF) patients. The present study aimed to investigate the effects of traditional Chinese exercise (TCE) on patients with CHF and the impact of exercise types and duration. Evaluation of randomized controlled trials (RCTs) of TCE in patients with CHF published since 1997 from PubMed, Embase, Web of Science, the Cochrane Library, Chongqing VIP, Wanfang Databases, and the China National Knowledge was performed. A total of 41 RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
0
0
Order By: Relevance
“…Patients with chronic NYHA grade III HF in the intervention group had significantly improved cardiac function (6MWT distance, LVEF, and NT-proBNP levels) and ADL capacity and decreased NYHA grade compared with the control group, which reflected the efficacy of the ESPCS intervention. Several studies have shown that regular rehabilitation exercises are beneficial for improving exercise ability and cardiac function [ 27 ], daily activity, LVEF [ 28 ], and serum NT-proBNP levels [ 29 ] in patients with CHF, which is consistent with the results of the current study. The participants in our study stated that they benefited from systematic health education and exercise training and that their heart function and ADL ability were improved through exercise and self-management.…”
Section: Discussionsupporting
confidence: 91%
“…Patients with chronic NYHA grade III HF in the intervention group had significantly improved cardiac function (6MWT distance, LVEF, and NT-proBNP levels) and ADL capacity and decreased NYHA grade compared with the control group, which reflected the efficacy of the ESPCS intervention. Several studies have shown that regular rehabilitation exercises are beneficial for improving exercise ability and cardiac function [ 27 ], daily activity, LVEF [ 28 ], and serum NT-proBNP levels [ 29 ] in patients with CHF, which is consistent with the results of the current study. The participants in our study stated that they benefited from systematic health education and exercise training and that their heart function and ADL ability were improved through exercise and self-management.…”
Section: Discussionsupporting
confidence: 91%
“…Traditional Chinese exercises emphasize the unity of body and mind, breathing and exhaling, which can play a role in unblocking meridians and regulating qi and blood. By regulating sympathetic and parasympathetic nerve activity, traditional Chinese exercises such as tai chi can promote the establishment of coronary collateral circulation and improve cardiac function (61).…”
Section: Exercise Prescription For Cardiac Rehabilitationmentioning
confidence: 99%